Yahoo Web Search

  1. Sort by

  1. ... force in the y-direction only: Weight of beam = vertical force on LHS cable + vertical force on RHS cable eqn 1: 8.76 * 10^3 = Flhs * sin(70...

    2 Answers · Science & Mathematics · 14/10/2014

  2. ...: 2009/2014 + 2019/n = a/b LHS: 2009/2014 + 2019/n = = [ 2009n + 2014(2019) ]/(2014n) ... substitute 2009 = (2*1004 + 1), 2014...

    3 Answers · Science & Mathematics · 12/10/2014

  3. ...of (x=1) vertical line : Re(z) <= 1 is the half-plane on LHS of line, the line included. here : position the complex : z0 = 3 - i which ...

    2 Answers · Science & Mathematics · 18/09/2014

  4. http://s1169.photobucket.com/user/chibuckt/media/IMG_20140808_0001_zps3addacb7.jpg.html?filters[user]=127216769&filters[recent]=1&sort=1&o=0

    3 Answers · Science & Mathematics · 11/08/2014

  5. ... T = 19.47 and 160.53 degrees. D. first one LHS / cotTsinT =cost/sint*sint=cost =cosTsinT/sintT=cosT...

    1 Answers · Science & Mathematics · 11/03/2015

  6. ... can't use Fgrav ~ m1*m2/d^2 like an equation because the LHS does not equal the RHS; it's not an equation. In fact, if...

    1 Answers · Science & Mathematics · 21/07/2014

  7. 4 - a - 1/2 = 2/3 (a +5) Simplify LHS 3.5 - a = 2/3 (a + 5) Multiply both sides by 3/2 5.25 - 1.5a...

    6 Answers · Science & Mathematics · 17/07/2014

  8. ...difference of two squares, Pythagorean identities to reduce the LHS to the RHS! sin^4(θ) - cos^4(θ) = (sin^2(θ) + cos^2(θ))*(sin^2(θ) - cos...

    2 Answers · Science & Mathematics · 03/06/2014

  9. LHS = cosh ( x + y ) = [e^(x + y) + e^(- x - y)]/2 RHS = cosh x cosh y + sinh x sinh y =[(e^x + e^-x)/2][(e^y + e^-y)/2] + [(e^x - e^-x)/2][(e^y - e^-y)/2] = (1/4)[e^(x + y) + e^(x - y) + e^(- x + y) + e^(- x - y)]   + (1/4)[e^(x + y) - e^(x - y) - e^(- x + y) + e^(- x - y)]  = (1/2)e^(x + y) + (1/2)e^(- x - y) = [e^(x + y) + e^(- x - y)]/2 so , LHS = RHS

    2 Answers · Science & Mathematics · 14/05/2014

  10. LHS = cos x tan^3x=sin x tan^2x = cosx[sin^3x/cos^3x] = [cosx/cos^3x]*[sinx*sin^2x] = [ 1/cos^2x]*[sinx*sin^2x] = sinx[sin^2x/cos^2x] = sinx tan^2x = RHS

    2 Answers · Science & Mathematics · 05/05/2014

  1. Try asking your question on Yahoo Answers